Small molecule inhibition of phosphatidylinositol-3,4,5-triphosphate (PIP3) binding to pleckstrin homology domains - Miao, Benchun; Skidan, Igor; Yang, Jinsheng; Lugovskoy, Alexey; Reibarkh, Mikhail; Long, Kai; Brazell, Tres; Durugkar, Kulbhushan A.; Maki, Jenny; Ramana, C. V.; Schaffhausen, Brian; Wagner, Gerhard; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The PI3-kinase (PI3K) pathway regulates many cellular processes, especially cell metabolism, cell survival, and apoptosis. Phosphatidylinositol-3,4,5-trisphosphate (PIP3), the product of PI3K activity and a key signaling molecule, acts by recruiting pleckstrin-homology (PH) domain-containing proteins to cell membranes. Here, we describe a new structural class of nonphosphoinositide small molecule antagonists (PITenins, PITs) of PIP3-PH domain interactions (IC50 ranges from 13.4 to 31 mu M in PIP3/Akt PH domain binding assay). PITs inhibit interactions of a number of PIP3-binding PH domains, including those of Akt and PDK1, without affecting several PIP2-selective PH domains. As a result, PITs suppress the PI3K-PDK1-Akt pathway and trigger metabolic stress and apoptosis. A PIT-1 analog displayed significant antitumor activity in vivo, including inhibition of tumor growth and induction of apoptosis. Overall, our studies demonstrate the feasibility of developing specific small molecule antagonists of PIP3 signaling.
Keywords: Anticancer; PIP3 antagonist

Optimization of the anti-cancer activity of the phosphatidylinositol-3 kinase pathway inhibitor PITENIN-1: switching thiourea with 1,2,3-triazole - Kommagalla, Yadagiri; Cornea, Sinziana; Riehle, Robert; Torchilin, Vladimir; Degterev, Alexei; Ramana, Chepuri V. (Medchemcomm, 2014)
We previously reported encouraging in vitro and in vivo anti-cancer activity of N-((3-chloro-2-hydroxy-5-nitrophenyl)carbamothioyl) benzamide (termed PITENIN-1). In the current work, we describe the structure-activity relationship study of the PIT-1 series, based on the replacement of a central thiourea unit with 1,2,3-triazole, which leads to increased liver microsomal stability, drug likeness and toxicity towards cancer cells.